Starfruit Maturity Stages and Fruit Packaging Type for Preserving Quality During Distribution - Sumiasih, Inanpi Hidayati; Nurainani, Nurainani (Department of Crop Science, Faculty of Agriculture, Andalas University, 2024)
One effort that can be made to reduce starfruit damage is harvesting at the right stage of maturity and choosing the proper packaging. The research objective was to obtain the right maturity stage and type of packaging to reduce the percentage of damage and preserve quality during the distribution process of starfruit. The research was carried out at the Trilogi University. The harvesting and packaging process was carried out at Attaqie Farm, East Java. The study was conducted from October 2022 to March 2023. The method used was a Completely Randomized Design with two factors; the first factor was the stage of maturity (S), consisting of 2 levels: S-4 and S-5). The second factor was the type of packaging composed of 4 levels: cardboard packaging (fruit sealed with newspaper); cardboard packaging (fruit sealed with newspaper and foam net); basket packaging (fruit sealed with newspaper); and basket (fruit sealed with newspaper and foam net), replicated three times. The variables observed were the percentage of fruit damage, °Hue value, taste scoring, Total Dissolved Solids (TDS), and Total Titratable Acidity (TTA). The research results showed that starfruit could still be accepted by consumers until the 6th day, with the best treatment in SK-4, which is basket packaging type (fruit sealed with newspaper and foam net). This treatment had good results, as indicated by the damage percentage value of 7.67%, taste score of above 3.5, TDS of 9.66, °Hue value of 99.89 with less bright colors, and TTA of 0.50.